Effect of TGA coated ZnS Quantum Dots on growth development of basil (Ocimum basilicum) plants - J. Luciano-Velázquez; I. López-Cruz; A.A. Rivera-Ortíz; G.D. Moreno-Echevarría; S.J. Bailón-Ruiz; M.L. López-Moreno (Plant Nano Biology, 2024)
Nanotechnology has captured the attention of the scientific community, particularly regarding the use of nanomaterials in various fields, including agriculture. In this field, nanoparticles are being studied as an alternative to traditional inorganic fertilizers. Previous studies have reported that nanoparticles may increase crop growth and yield. However, the use of nanoparticles higher than 10 nm may cause harm and toxicity in some plant species, and some of these nanomaterials are not water-soluble or chemically stable. The objective of this study is to evaluate the effect of water-stable TGA coated ZnS Quantum Dots (QDs) on the growth of Ocimum basilicum (basil) plants. QDs are known for their small size (less than 10 nm) and potential biocompatibility depending on their organic coating. In this research, the nanostructures synthesized were mostly spherical with an average size of 2.4 nm and crystalline structure resembling zinc blende. The EDS spectrum showed the elemental composition of the QDs, with 49.0 % zinc and 51.0 % sulfur, and the TGA coated ZnS QDs exhibited a fluorescent peak at 423 nm, which is characteristic of this material. These QDs were added to basil seedlings to promote plant growth and development. Results showed an increase in total chlorophyll content by 11 % in plants exposed to 250 ppm of TGA coated ZnS QDs and 12 % for plants exposed to 500 and 1000 ppm. Highest concentration of Mg (21 % more than control plants) was found in plants exposed to 500 ppm of TGA coated ZnS QDs. An increase in K and Ca uptake was observed in plants exposed to 750 ppm QDs (by about 15 % and 24 % respectively). Plants exposed to QDs at 1000 ppm increased Cu, Mn, and Fe by about 36 %, 86 %, and 523 % respectively. Additionally, plants exposed to 500 ppm QDs increased Zn concentration in leaves by about 89 %. QDs, covered with TGA and measuring 2.4 nm, enhanced nutrient absorption in roots due to the high contact surface between the QDs and roots. The small size of the QDs enables transport within plants, traveling across both the xylem and phloem.